2011
DOI: 10.1002/asi.21706
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and measuring metadata completeness

Abstract: Completeness of metadata is one of the most essential characteristics of their quality. An incomplete metadata record is a record of degraded quality. Existing approaches to measure metadata completeness limit their scope in counting the existence of values in fields, regardless of the metadata hierarchy as defined in international standards. Such a traditional approach overlooks several issues that need to be taken into account. This paper presents a fine‐grained metrics system for measuring metadata complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Bruce and Hillmann (2004) enhanced and modified these six indicators for the library community. Margaritopoulos, Margaritopoulos, Mavridis, and Manitsaris (2012) found that completeness of metadata is one of the most essential characteristics of their quality; the authors presented a fine-grained metrics system for measuring metadata completeness, based on field completeness. Margaritopoulos, Margaritopoulos, Mavridis, and Manitsaris (2012) found that completeness of metadata is one of the most essential characteristics of their quality; the authors presented a fine-grained metrics system for measuring metadata completeness, based on field completeness.…”
Section: Metadata Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bruce and Hillmann (2004) enhanced and modified these six indicators for the library community. Margaritopoulos, Margaritopoulos, Mavridis, and Manitsaris (2012) found that completeness of metadata is one of the most essential characteristics of their quality; the authors presented a fine-grained metrics system for measuring metadata completeness, based on field completeness. Margaritopoulos, Margaritopoulos, Mavridis, and Manitsaris (2012) found that completeness of metadata is one of the most essential characteristics of their quality; the authors presented a fine-grained metrics system for measuring metadata completeness, based on field completeness.…”
Section: Metadata Qualitymentioning
confidence: 99%
“…The enhanced criteria include completeness, accuracy, provenance, conformance to expectation, logical consistency, coherence, timeliness, and accessibility. Margaritopoulos, Margaritopoulos, Mavridis, and Manitsaris () found that completeness of metadata is one of the most essential characteristics of their quality; the authors presented a fine‐grained metrics system for measuring metadata completeness, based on field completeness. Citation quality and its correlation with retrieval/recommendation ranking performance in this framework, unfortunately, have rarely been investigated.…”
Section: Related Researchmentioning
confidence: 99%
“…Typical indicators and dimensions of quality of metadata records in LORs include the ones presented in Table I, as they have been the basis for a number of studies focusing on the metadata quality assessment of LORs (Yen and Park, 2006;Ma et al, 2010;Ochoa et al, 2011;Westbrook et al, 2012;Margaritopoulos et al, 2012).…”
Section: Quality Of Metadatamentioning
confidence: 99%
“…More specifically, the data used to describe the learning objects (i.e. its metadata) -a key enabler for the deployment of efficient search mechanisms and services on top of LORs -seems to be incomplete, as several studies indicate (Najjar et al, 2003;Hughes, 2004;Shreeves et al, 2005;Yen and Park, 2006;Ma et al, 2010;Manouselis et al, 2010;Ochoa et al, 2011;Westbrook et al, 2012;Margaritopoulos et al, 2012). Actually, the time span of these studies indicates that the problem has been around for almost a decade and some of these authors point out even more serious quality problems than the completeness of the records, with issues related to the content of the completed metadata records in terms of validity and correctness.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve metadata in an information system, reviewing the types of data and ways that they are being used for particular elements in records can be a way of isolating particular issues involved with the metadata creation process. 3 Hopefully this would lead to an improvement in the overall consistency of records.…”
Section: Introductionmentioning
confidence: 99%